Analysis of Rock β-Dynamic Parameters and the Stability of Earthquake Dangerous Rocks Based on PFC - Yun Tian; Lin-feng Wang; Biao Zeng; Hong-hua Jin (Advances in Civil Engineering)
Mesoparameters of rock materials are the main factors affecting the macromechanical properties of dangerous rock slopes. Based on the principle of particle flow and synthetic rock mass technology (SRM), the influence of mesoparameters on macromechanical properties is investigated by calibrating mesoparameters of rock materials at depth for a rock sequence in Beichuan Qiang Autonomous County, Sichuan Province, China. By combining these parameters with conventional and dynamic cycle triaxial tests, sensitivity analysis of rock β-parameters was completed. As a result, the reliability of mesoparameters in the simulation of dangerous rocks is strengthened, providing a basis to examine the failure mechanism of earthquake dangerous rocks in this region. Results indicate that, in the triaxial test, sandstone failed in tension, and brittleness gradually weakened as confining pressure increased. Mudstone recorded shear failure, and the characteristic value of brittle attenuation showed a V-shaped change with increasing confining pressure. Under cyclic loading, cracks had a degrading effect on the damping ration (β) and the damping coefficient (C) of sandstone. Mudstone recorded relatively low β and low brittleness whilst sandstone had high β and high brittleness. In rock materials, βn is more sensitive than βs in mechanical properties. When the value of the βn-parameter was between 0.2 and 0.3 and the value of the βs-parameter was between 0.2 and 0.6, rock brittleness was more stable, and the reflected macroscopic mechanical properties were the most authentic. By using a deepened mesoparameter trial adjustment method, the failure mode of the Particle Flow Code (PFC) dangerous rock model near provincial highway 205, simulated under conditions for the Wenchuan earthquake, indicated a tensile fracture-horizontal slip failure. The simulated failure mode was consistent with that of real dangerous rocks, with the failure trend being concentrated between the first and the third layer of the rock mass.